2014
DOI: 10.1111/pim.12091
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies are involved in the protective immunity induced in mice by Schistosoma mansoni schistosomula tegument (Smteg) immunization

Abstract: The Schistosoma mansoni schistosomula tegument (Smteg) plays an important role in triggering the host immune response and mice immunization with Smteg formulated with Freunds adjuvant or alum + CpG induce partial protection against S. mansoni infection associated with an increased antibody production. In this study, we investigated the role of these antibodies in parasite killing both in vitro and in vivo. We demonstrated that these antibodies were able to bind to the surface of S. mansoni recently transformed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
4
15
0
Order By: Relevance
“…De Melo et al [19] detected significant levels of antischistosomula tegument (Smteg) IgG antibodies in the sera of mice injected with Smteg compared to control group. This is also is in accordance with the results of de Melo et al [20] who transferred sera from mice immunized with Smteg or Smp-80 to a naïve recipient and that was able to induce partial protection against challenge infection. Our data allowed us to speculate that, PZQ administration enhanced the humoral response in naïve mice.…”
Section: Discussionsupporting
confidence: 92%
“…De Melo et al [19] detected significant levels of antischistosomula tegument (Smteg) IgG antibodies in the sera of mice injected with Smteg compared to control group. This is also is in accordance with the results of de Melo et al [20] who transferred sera from mice immunized with Smteg or Smp-80 to a naïve recipient and that was able to induce partial protection against challenge infection. Our data allowed us to speculate that, PZQ administration enhanced the humoral response in naïve mice.…”
Section: Discussionsupporting
confidence: 92%
“…These studies demonstrate that antibodies are involved in parasite elimination [19,23,24]. Our results show a vigorous humoral immune response, with significant levels of IgG, IgG1 and IgG2a, and IgE in infected/treated Balb/c mice immunized with rSm22.6 or rSm29 plus Freund’s adjuvant.…”
Section: Discussionsupporting
confidence: 60%
“…The schistosomula were cultured for 3 hours at 37°C in medium. Later, the schistosomula were incubated with immune sera and FITC-conjugated anti-mouse IgG, as described [19]. Briefly, schistosomula were washed three times with DMEM medium by centrifugation at 1800g/5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Sera obtained from donor immunized mice and baboons have been shown to protect recipients against subsequent schistosome challenge when passively transferred (Byram et al 1979; Doenhoff et al 1979; Mangold and Dean 1986; Melo et al 2014; Torben et al 2011). Studies utilizing schistosome non- and/or semi-permissive host such as rats have shown that resistance to schistosome infections as well as mechanism of schistosome killing are almost entirely humoral mediated by high IgG antibodies (Knopf et al 1977; Wilson et al 2008).…”
Section: Discussionmentioning
confidence: 99%